Complete mitochondrial genome of orthotomus sutorius (passeriformes: cisticolidae) - Hui Gao; Zhicheng Yao; Yanyan Zhao; Minhao Chen; Zongzhi Li; Xue Meng Zhou; Yuanguang Wen; Xiaoguo Zhou; Yongjie Huang (Mitochondrial DNA. Part B. Resources)
The complete mitogenome of Orthotomus sutorius Pennant, 1769 this species was sequenced using an Illumina Novaseq platform. It is 16,982 bp in length and consists of 13 protein-coding genes (PCGs), 22 tRNA genes, two rRNA genes (12S rRNA and 16S rRNA) and a control region (CR). We reconstructed a phylogenetic tree based on the mitogenome sequences of 10 species from family Cisticolidae with its adjacent families, as well as one outgroup. Phylogenetic analysis indicated that Orthotomus sutorius is well clustered with Cisticola juncidis. The new mitogenome data would provide useful information for evolutionary research on O. sutorius and the family Cisticolidae.